2008
DOI: 10.1016/j.scitotenv.2007.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater nitrogen composition and transformation within a moorland catchment, mid-Wales

Abstract: The importance of upland groundwater systems in providing a medium for nitrogen transformations and processes along flow paths is investigated within the Afon Gwy moorland catchment, Plynlimon, mid-Wales. Dissolved organic nitrogen (DON) was found to be the most abundant form of dissolved nitrogen (N) in most soils and groundwaters, accounting for between 47 and 72% of total dissolved nitrogen in shallow groundwater samples and up to 80% in deeper groundwaters. A significant correlation between dissolved organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
0
12
1
Order By: Relevance
“…DON can comprise a significant proportion of the total N load in some circumstances, up to 90% in forested glacial outwash in Canada with concentrations increased by anthropogenic impacts (Kroeger et al, 2006). Lapworth et al (2008b) also found DON was the most abundant form of dissolved N in both soils and groundwaters in a moorland catchment, accounting for between 47 and 72% in shallow groundwater samples and up to 80% in deeper groundwaters.…”
Section: Nitrogen Fate and Transport In Groundwatermentioning
confidence: 76%
See 3 more Smart Citations
“…DON can comprise a significant proportion of the total N load in some circumstances, up to 90% in forested glacial outwash in Canada with concentrations increased by anthropogenic impacts (Kroeger et al, 2006). Lapworth et al (2008b) also found DON was the most abundant form of dissolved N in both soils and groundwaters in a moorland catchment, accounting for between 47 and 72% in shallow groundwater samples and up to 80% in deeper groundwaters.…”
Section: Nitrogen Fate and Transport In Groundwatermentioning
confidence: 76%
“…For sites in upland mid Wales, Lapworth et al (2008b) found the range of DOC in groundwater ranging from 0.4 mg/L to 10.6 mg/L with a median of 2.1 mg/L. All samples were below 4.3 mg/L except one.…”
Section: Literature Datamentioning
confidence: 91%
See 2 more Smart Citations
“…chemical and microbiologically mediated nutrient and weathering transformations on particle surfaces (Boulton et al 1998;Gooseff et al 2002;Greenwald et al 2008). Understanding these processes is important and may vary depending on the hydrology, land use, ecological sensitivity and management of a particular system: to determine the sustainable limits of abstraction (Cook et al 2003) in a water-sensitive system, to understand the hydrological function of the riparian zone (Fernald et al 2001;) and/or to assess the function of the riparian zone in regulating biogeochemical processes (Findlay et al 1993;Jones et al 1995;Hill 1996;Jarvie et al 2006a;Rassam et al 2006;Lapworth et al 2008).…”
mentioning
confidence: 99%